PROGRAM PENDAMPINGAN ANAK CINTA MEMBACA (PANCA) BAGI SISWA BELUM LANCAR MEMBACA DI SDN I KALIWADAS - Maylitha, Evi; Maharani, Faniar Sesara; Wahyuningrum, Fanny; Rachmaali, Farah Fithriya; Fadhilah, Farah Nur; Rachmat, Irfan Fauzi; Susylawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the PANCA (Supporting Children’s Love of Reading) program and to determine the development of students’ reading abilities after participating in the support activities at SDN 1 Kaliwadas. This study employs a qualitative descriptive approach, with the research subjects being elementary school students who struggle with reading. Data collection techniques included observation, documentation, and tracking students’ progress throughout the program. The PANCA program was implemented using a phonics-based method in a fun and supportive learning environment. The results of the study indicate that the PANCA program has a positive impact on students’ reading skills. Students demonstrated progress in recognizing letters, sounding out syllables, reading simple words, and increased self-confidence in reading activities. Additionally, the interactive learning environment helped students become more active and motivated in learning to read. Thus, the PANCA program can serve as an alternative reading support activity to assist elementary school students who have not yet mastered reading.